Answer:
![(2^3)^2 = 64](https://img.qammunity.org/2021/formulas/mathematics/high-school/x6mx7gdsltkx64q2fh3f17n21bfoqrxjpm.png)
Explanation:
Option 1:
Using the following rule:
![(a^n)^m = a^(nm)](https://img.qammunity.org/2021/formulas/mathematics/high-school/s1fu04xsz0lfmm4pgz93d950ln8pvigkk7.png)
Put in our expression,
a = 2
n = 3
m = 2
![(a^n)^m = a^(nm)](https://img.qammunity.org/2021/formulas/mathematics/high-school/s1fu04xsz0lfmm4pgz93d950ln8pvigkk7.png)
![(2^3)^2 = 2^(3*2)=2^6=64](https://img.qammunity.org/2021/formulas/mathematics/high-school/ssuz2q55kycmjv8dmdyes8w5r7is3qf60y.png)
Option 2:
Using the following rule:
![a^n * a^m = a^(n+m)](https://img.qammunity.org/2021/formulas/mathematics/high-school/22ij3w0wkhrkuwfn6vvsp7h7w85dgarz6h.png)
Since our expression is the same as multiplying 2³ with itself, we can write it as a multiplication.
![(2^3)^2 = 2^3 * 2^3](https://img.qammunity.org/2021/formulas/mathematics/high-school/1h2c6thi8bkqmg82k0sob2eadm0n9fenei.png)
If we compare this with
, we can see that
a = 2
n = 3
m = 3 (in this case, n and m are equal)
![a^n*a^m = a^(n+m)](https://img.qammunity.org/2021/formulas/mathematics/high-school/d8j9tazwx78hcvf2kdnpv39uweh1ueq1jh.png)
![2^3*2^3 = 2^(3+3) = 2^6 = 64](https://img.qammunity.org/2021/formulas/mathematics/high-school/hqnlqxh3rmkmn4rplsl7j63gujb89ticpx.png)
Answer:
![(2^3)^2 = 64](https://img.qammunity.org/2021/formulas/mathematics/high-school/x6mx7gdsltkx64q2fh3f17n21bfoqrxjpm.png)